Polskie nekrologi w prasie – sposoby wartościowania językowego - Jakosz, Mariusz (Postscriptum Polonistyczne, 2020)
The author of the article analyzes Polish obituary notices published in „Gazeta Wyborcza” (the nationwide newspaper published daily). In the beginning the characteristic features and types of this genre has been discussed. The author attempts to explain also how valuation is understood in linguistic context and through which means it is realized. He has fully analyzed selected obituary notices regarding them from linguistic and axiological perspective. His aim has been to show what was being valuated in obituary notices and how it was manifested in different elements of such texts (initial formula, identification and characteristics of a person who died, the ending of the obituary notice).